Inventory Planning and Control on Packaging Raw Materials in the Bottled Drinking Water Business (AMDK) PT XYZ Samarinda City - Wahyudi, Muhammad; Wahyuda, Wahyuda; Sitania, Farida Djumiati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The production of bottled drinking water (AMDK) has growth of 10.4% from 2010 to 2019. One of the AMDK companies located in Samarinda City is PT XYZ. The produced product is water packaged in 220 ml glass containers. The raw materials for the 220 ml water packaging product include cups, cup lids, straws, cardboard boxes, and cardboard dividers. The AMDK business operated by PT XYZ has only been in operation since 2021, and there is currently no inventory planning and control for the raw materials used in the packaging of the 220 ml AMDK product. This has resulted in a lack of packaging raw material inventory, thus hindering the AMDK production process in the company. Based on this issue, this research is conducted to plan and control the inventory of 220 ml water packaging raw materials at PT XYZ, in order to optimize inventory costs and meet consumer demand for AMDK. Inventory planning and control are carried out using the Material Requirement Planning (MRP) method, and the method used to determine the lot size is the Economic Order Quantity (EOQ) method with shipping capacity constraints. Based on the data processing conducted, the optimal order quantities using the EOQ method with shipping capacity constraints for each packaging raw material are 15.000 pieces for cardboard and cardboard dividers with an inventory cost of IDR 267.112.900. 1.500.000 pieces for straws with an inventory cost of IDR 46.831.630. 540.000 pieces for cups with an inventory cost of IDR 232.026.718. 150 rolls for cup lids with an inventory cost of IDR 87.125.910. The total inventory cost for packaging raw materials for 220 ml AMDK cups is IDR 633.097.158.